Capacity issues at the front door. (2nd September 2019) - Lepping, Peter
Abstract : Decision-making capacity is often overestimated by clinicians. An average of one third of patients lack capacity to make complex decisions and clinicians should be alert to such a possibility. Cognitive impairment, acute infection, intoxication and other common medical and psychiatric problems can impair patients' capacity. The Mental Capacity Act 2005 has to be applied when treating patients who lack capacity. The main decision maker for a proposed treatment or investigation is responsible for assessing capacity. However, all clinicians have to consider and assess capacity, and act in a patient's best interests if he/she lacks capacity.